A Smart Monitoring of Hybrid Mini Wind -Solar System Using IoT Application - Kamaluddin, Ahmad Syahid; Jumaat , Siti Amely (Evolution in Electrical and Electronic Engineering, 2022)
Nowadays renewable energy systems becoming the most reliable way to generate electricity to exchange with non-renewable energy such as coal and gases. The objective of the paper is to develop a monitoring system for a hybrid mini-wind-solar system. Thus, the project has addressed the development of a prototype using NodeMcu ESP8266 as the main microcontroller. For the project development, the voltage sensor and current sensor function to monitor the mini hybrid wind-solar system's performance. The NodeMcu ESP8266 board is also through used to transfer data between system devices to the Blynk platform. A Blynk is a Platform used to achieve the Internet of Things (IoT) for this project. A mini hybrid wind-solar system data collection was conducted to evaluate hybrid system performance by directly automatic reading the data from the Blynk Application. The project was tested at Parit Sulong, Batu Pahat, Johor from 18th until 24th June 2021. Based on the result, the hybrid system was charging a 12V battery and turning on a 9V 3W bulb and a DC motor as a load of the system. The minimum and maximum power generated is 0.65W and 2.77W with the minimum and maximum wind speeds of 0.3m/s, and 2.4m/s, respectively.